Tilapia growth performance and body physical index given synbiotic feed at different salinities. Issue 1 (1st January 2023) - Rahmi, R; Akmal, A; Nisaa, K; Sudrajat, I; Relatami, A N R; Tampangallo, B R; Ikbal, M
Abstract: Tilapia saline is a fishery commodity with a fairly large market prospect but has problems with slow growth performance, affecting the speed of its production. This study aims to determine the best growth performance with the body's physical index of tilapia at different salinities using the synbiotic feed. The synbiotic feed is given with probiotic Bacillus subtilis 105 CFU/mL density and banana flour prebiotic 1%. This study used five different salinity treatments (A. 0 ppt; B. 5 ppt; C. 10 ppt; D. 15 ppt; E. 20 ppt) with a weight of tilapia 3, 35±0, 5g each 20 fish/aquarium. The results showed that mortality, FCR, weight gain (WG), and feed efficiency showed significant results in the 15 ppt salinity treatment compared to other treatments. The HIS, DSI, and Condition Factor (K) values were not significantly different (P>0, 05), but the IPF values were significantly different (P<0, 05) from other treatments. The average treatment at 15 ppt salinity gave optimal growth performance and physical body index, especially IPF in tilapia fry.